Agronomic Strategies for Vegetative Propagation of Pterocarpus Mildbraedii - N A, Okoli; A Z, Obasi; E, Offorji (Canadian Journal of Agriculture and Crops, 2022)
Pterocarpus mildbraedii is faced with the problem of extinction caused mainly by deforestation and urbanization. This study was carried out to determine ways to enhance root development and domestication of Pterocarpus mildbraedii in southeastern Nigeria. The first experiment was done to determine the effect of nursery media and stem cutting length on sprouting and growth of Pterocarpus mildbraedii. Treatments consisted of three nursery media; (Standard nursery media, top soil and sawdust) and four stem cutting lengths; (5, 10, 15 and 20 cm). The experiment was a 3 x 4 factorial arrangement laid out in Complete Randomized Design. In the second experiment, treatments consisted of five (5) hours of priming (0, 12, 24, 36 and 48 hours) in coconut water arranged in Complete Randomized Design. Results from the first experiment showed that nursery media did not significantly (P ≤ 0.05) affect sprouting and growth of Pterocarpus mildbraedii seedlings. However, stem cutting length significantly affected sprouting and growth of the shoots. Stem cuttings of 15 and 20 cm length sprouted earliest and had vigorous growth than cuttings of 5 and 10 cm lengths. However, shoots wilted one month after sprouting. Results from second experiment showed that stem cutting primed in coconut water for 24 hours significantly produced highest no of roots (12.00), longest root (9 cm) and had highest fresh biomass (11.55 g) while control had no roots and least fresh biomass (3.02 g). The results showed the possibility of vegetative propagation of Pterocarpus mildbraedii and domestication in southeastern Nigeria.